2020
DOI: 10.1111/ans.16072
|View full text |Cite
|
Sign up to set email alerts
|

Predicting survival in non‐functional pancreatic neuroendocrine tumours

Abstract: Background: Owing to the limited prevalence and heterogeneity, it is difficult to predict long-term survival of non-functional pancreatic neuroendocrine tumours (NF-PNETs).This study aimed to evaluate the factors predicting disease-specific survival (DSS) for welldifferentiated NF-PNETs. Methods: Data were collected retrospectively from 256 patients with pancreatic neuroendocrine tumours who underwent surgical resection between January 2009 and December at our institution. Of these, 103 NF-PNETs (40%) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Unfortunately, most studies investigating vascular/lymphovascular invasion as prognostic factors in resected PanNETs neither specified nor separated venous invasion from small vessel invasion. The results from these studies were not very consistent 19–32. While most studies showed that lymphovascular/vascular invasion were associated with recurrence-free survival only in univariate analysis,23,25,27,28,31,32 a number of other studies demonstrated either significant association with recurrence-free survival in multivariate analysis with a hazard ration ranging from 2.8 to 6.5,19,22,29,30 or no prognostic impact in all analyses 21,26.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Unfortunately, most studies investigating vascular/lymphovascular invasion as prognostic factors in resected PanNETs neither specified nor separated venous invasion from small vessel invasion. The results from these studies were not very consistent 19–32. While most studies showed that lymphovascular/vascular invasion were associated with recurrence-free survival only in univariate analysis,23,25,27,28,31,32 a number of other studies demonstrated either significant association with recurrence-free survival in multivariate analysis with a hazard ration ranging from 2.8 to 6.5,19,22,29,30 or no prognostic impact in all analyses 21,26.…”
Section: Discussionmentioning
confidence: 90%
“…The results from these studies were not very consistent 19–32. While most studies showed that lymphovascular/vascular invasion were associated with recurrence-free survival only in univariate analysis,23,25,27,28,31,32 a number of other studies demonstrated either significant association with recurrence-free survival in multivariate analysis with a hazard ration ranging from 2.8 to 6.5,19,22,29,30 or no prognostic impact in all analyses 21,26. The recurrence pattern was reported in some studies, with the liver being the most common site followed by regional lymph nodes 28,29.…”
Section: Discussionmentioning
confidence: 93%
“…Of all the assessed factors, tumor grade III–IV was most highly associated with LNM (OR 7.90), although the proportion of these patients was relatively low. Tumor grade has been considered the main determinant of the malignancy of NF-PNETs, which is associated with not only the metastasis potential ( 9 , 14 ) but also the long-term survival ( 15 , 24 ). With the support of developed image technology, fine-needle aspiration biopsy (guided by endoscopic ultrasound (EUS), US, or CT) is recommended to evaluate the tumor grade preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor grade is the crucial determinant of the biological aggressiveness of PNETs. Additionally, it is suggested to be associated with lymph node involvement ( 7 ), tumor recurrence ( 8 ), and overall prognosis ( 9 ). According to the 2010 World Health Organization (WHO) classification criteria ( 10 ), tumor grade is defined numerically by the proliferative indicator Ki-67, in which low-grade (grade 1 (G1)) tumors have a Ki-67 index from 0% to 2%, intermediate-grade (G2) tumors have a Ki-67 index from 3% to 20%, and high-grade (G3) tumors have a Ki-67 index greater than 20%.…”
Section: Introductionmentioning
confidence: 99%